PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PAPAN PINTAR TERHADAP HASIL BELAJAR ILMU PENGETAHUAN ALAM DAN SOSIAL MATERI “AKU DAN KEBUTUHANKU” SISWA KELAS IV UPTD SD NEGERI OEBOBO 2 - Kabba, Yosefina; Kopong Tokan, Moses; Y. N. Adoe, Treesly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the learning outcomes of students using the Problem Based Learning model on the material "I and my needs". The type of research used Pre-Experimental Design with a One-Group Pretest-Postest Design research design. The subjects used were all fourth grade students of UPTD SD Negeri Oebobo 2 totaling 27 people. The sampling technique used the Non Probability sampling technique with saturated sampling, where the entire population was sampled. Data collection techniques and instruments in the form of tests and observation sheets. The test instruments given were in the form of pretests and posttests to measure learning outcomes. Before being used, the test instruments were first tested for validity and reliability. After the data was collected, they were analyzed using a hypothesis test. The results showed that the average posttest score was 84.07> the average pretest score of 57.96. In addition, the results of hypothesis testing with a paired sample T-test showed that the significance value (2-tailed) was 0.000. This shows that the significance level value (2-tailed) <0.05, according to the basis for making this test decision that if the significance level value (2-tailed) <0.05, then the learning outcomes differ significantly between the pretest and posttest data. Therefore, the results of the study indicate a significant influence between the Problem Based Learning model assisted by smart board media on the learning outcomes of science subjects and the needs of grade IV students of UPTD SD Negeri Oebobo 2.